Fear is associated with attrition of first‐time whole blood donors: A longitudinal examination of donor confidence and attitude as potential mediators. Issue 12 (18th September 2021) - France, Christopher R.; France, Janis L.; Himawan, Lina K.; Duffy, Louisa; Kessler, Debra A.; Rebosa, Mark; Rehmani, Shiraz; Frye, Victoria; Shaz, Beth H.
Abstract: Background: Elevated fear and anxiety regarding donation‐related stimuli (e.g., needles, pain, blood, fainting) has been associated with reduced blood donor recruitment and retention. The present longitudinal study tests the notion that this inverse relationship may be accounted for by lower donation confidence and more negative donation attitudes among fearful first‐time donors. Study Design and Methods: In a sample of 1479 first‐time whole blood donors [67.9% female; mean age = 19.3 (standard deviation (SD) = 2.5) years], path analyses were conducted to examine relationships among donor ratings of fear of blood draw and donation anxiety obtained approximately 1 week after donation, donation confidence and attitudes assessed approximately 6 weeks later, and donation attempts over the 14 months following the original donation. Results: Path analyses indicated that both fear of blood draws and donation anxiety were associated with fewer attempted donations, and that these effects were indirectly mediated by a combination of lower donor confidence and more negative donation attitudes. Conclusion: Because retention of new blood donors is essential to maintain a healthy blood supply, the results of the present study suggest that first‐time donors should be assessed for fear and anxiety so that appropriate strategies can be provided to address their concerns, bolster their confidence and attitudes, and ultimately promote their long‐term retention.